Surface‐Assisted Synthesis of N‐Containing π‐Conjugated Polymers. Issue 19 (22nd May 2022) - Sánchez‐Grande, Ana; Urgel, José I.; García‐Benito, Inés; Santos, José; Biswas, Kalyan; Lauwaet, Koen; Gallego, José M.; Rosen, Johanna; Miranda, Rodolfo; Björk, Jonas; Martín, Nazario; Écija, David
Abstract: On‐surface synthesis has recently emerged as a powerful strategy to design conjugated polymers previously precluded in conventional solution chemistry. Here, an N‐containing pentacene‐based precursor (tetraazapentacene) is ex‐professo synthesized endowed with terminal dibromomethylene (:CBr2 ) groups to steer homocoupling via dehalogenation on metallic supports. Combined scanning probe microscopy investigations complemented by theoretical calculations reveal how the substrate selection drives different reaction mechanisms. On Ag(111) the dissociation of bromine atoms at room temperature triggers the homocoupling of tetraazapentacene units together with the binding of silver adatoms to the nitrogen atoms of the monomers giving rise to a N‐containing conjugated coordination polymer (P1 ). Subsequently, P1 undergoes ladderization at 200 °C, affording a pyrrolopyrrole‐bridged conjugated polymer (P2 ). On Au(111) the formation of the intermediate polymer P1 is not observed and, instead, after annealing at 100 °C, the conjugated ladder polymer P2 is obtained, revealing the crucial role of metal adatoms on Ag(111) as compared to Au(111). Finally, on Ag(100) the loss of :CBr2 groups affords the formation of tetraazapentacene monomers, which coexist with polymer P1 . Our results contribute to introduce protocols for the synthesis of N‐containing conjugated polymers, illustrating the selective role of the metallic support in the underlying reaction mechanisms. Abstract : A tetraazapentacene precursor endowed with =CBr2 groups is synthesized to steer unprecedented on‐surface polymerizations. On Ag(111) an intermediate conjugated coordination polymer (P1 ) is detected, which evolves towards a conjugated ladder polymer P2 upon annealing. Counterintuitively, on Au(111) P2 is found at a much lower annealing temperature, without the observation of P1, thus highlighting the decisive role of the substrate.